Apixaban for the prevention of thromboembolism in immunomodulatory‐treated myeloma patients: Myelaxat, a phase 2 pilot study. Issue 6 (1st April 2019) - Pegourie, Brigitte; Karlin, Lionel; Benboubker, Lotfi; Orsini‐Piocelle, Frédérique; Tiab, Mourad; Auger‐Quittet, Sophie; Rodon, Philippe; Royer, Bruno; Leleu, Xavier; Bareau, Benoit; Cliquennois, Manuel; Fuzibet, Jean‐Gabriel; et al.
Abstract: The risk of venous thromboembolism (VTE) is higher in myeloma patients receiving immunomodulatory compounds. A VTE prophylaxis using low‐molecular‐weight heparin or aspirin is therefore proposed. Apixaban is an oral direct anti‐Xa. Several studies have shown the efficacy and safety of apixaban in VTE prophylaxis compared to enoxaparin. The objective of this prospective phase 2 pilot study was to assess the risk of VTE and bleeding in patients with myeloma treated with immunomodulatory compounds lenalidomide (len) or thalidomide (thal), using apixaban in a preventive scheme. Myeloma patients requiring Melphalan‐Prednisone‐Thalidomide in the first line, or Lenalidomide‐Dexamethasone in the relapse setting received apixaban, 2.5 mg x 2/day for 6 months. Venous (pulmonary embolism—PE, or symptomatic proximal or distal deep vein thrombosis—DVT, or all proximal asymptomatic events detected by systematic proximal bilateral compression ultrasound) or arterial thrombotic events, and bleeding events (ISTH 2005) were registered. One hundred and four patients were enrolled (mean age 69.8 ± 7.8 years), 11 in first line and 93 in relapse. Two venous thrombotic events were observed, for example, an asymptomatic proximal DVT and a symptomatic distal DVT, in the context of apixaban stopped 14 days before, due to lenalidomide‐induced thrombocytopenia. No PE or arterial cardiovascular events were reported. Only one major and 11 CRNM hemorrhages were reported. These data must now be confirmed on a randomized large study.